An experimental study of NO reduction by biomass reburning and the characterization of its pyrolysis gases. (1st January 2015) - Shu, Yun; Zhang, Fan; Wang, Hongchang; Zhu, Jinwei; Tian, Gang; Zhang, Chen; Cui, Yutao; Huang, Jiayu
Highlights: Biomass type had a significant influence on NO reduction efficiency. Difference in NO reduction was due to difference in yield of pyrolysis gas of biomass. Hydrocarbons (mainly CH4 ) were mainly responsible for NO reduction. Abstract: The reduction of NO by reburning using three biomass samples (rice husk, sawdust and corncob) was investigated in a horizontal fixed-bed quartz reactor. The temperatures were ranging from 800 to 1200 °C. The influence of the oxygen concentration entering the reburning zone, the particle size of the biomass and the initial NO concentration on the NO reduction efficiency were studied experimentally. In order to improve the understanding of the relative contribution of each of the pyrolysis gases on the NO reduction, the CO, H2, hydrocarbons (mainly CH4 ), HCN, and NH3 concentrations in the outlet gas from the reburning zone were measured at combustion temperatures of 800–1200 °C. The experimental results indicated that the biomass type had a significant influence on the NO reduction efficiency. The maximum NO reduction efficiency of sawdust reburning (55 ± 2.4%) was much higher than those of rice husk reburning (43 ± 1.8%) and corncob reburning (44 ± 2.1%). For reburning with sawdust, a highly efficient NO reduction was achieved at oxygen inlet concentrations of 0–1 vol%, particle sizes of 160–370 μm and initial NO concentration of 800 ppmv. For the present operating conditions, the difference in NO reduction for the three biomass samples could be ascribed to differences in the yield of pyrolysis gases through the homogeneous reactions. Hydrocarbons (mainly CH4 ) were the key species for reducing the emissions of NO, whereas CO and H2 had little effect on NO reduction. The sum of the HCN and NH3 concentrations could reflect the tendency for the conversion of the NO entering the reburning zone into N2 .